IMPLEMENTASI KEBIJAKAN BEBAS VISA KUNJUNGAN DI PROVINSI SULAWESI UTARA - MONINTJA, YEREMIA; RARES, JOYCE JACINTA; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2018)
Indonesia is a country that has very many tourist objects to go. With that, Indonesia has the capital to attract foreign tourist to visit Indonesia. The presence off oreign tourists does have a good influence on Indonesia, especially in economic sector. To support this, the Presidential Regulation No. 21 of 2016 concerning visa-free visits was made. Policies taken by the government to make it easier for foreign countries to visit Indonesia. Including the province of North Sulawesi, which is now the focus of research. By using qualitative methods, so as to obtain data through direct observation and in-depth interviews with several informants. The results of this study indicatethat, in terms of communication has been going well. Then in terms of resources it is good, butt here must be additional staff becauseof a short age of workers. Then from the disposition or attitude of the employee, it has gone very well. From the bureaucratic structure it has also been arranged very well. However, in this policy, there are still problems, which is theuse of visa-free visits for those who have not fully understood this policy. Then, there are too many countries granted visa exemptions to Indonesia, whichis 169 countries.Keywords: implementation, visit visa-free policy.